2011
DOI: 10.1002/adfm.201002493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Amyloid Fibrils Using Coarse‐Grained Normal Mode Analysis

Abstract: Recent experimental studies have shown that amyloid fi bril formed by aggregation of β peptide exhibits excellent mechanical properties comparable to other protein materials such as actin fi laments and microtubules. These excellent mechanical properties of amyloid fi brils are related to their functional role in disease expression. This indicates the necessity of understanding how an amyloid fi bril achieves the remarkable mechanical properties through self-aggregation with structural hierarchy. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
74
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 64 publications
13
74
0
Order By: Relevance
“…[29] From their studies, the lowest frequency bending mode behavior was found to be similart ot he bending mode behavior of our model. In addition, the general trend of our resultsi sc onsistent with otherh IAPP results obtained by using the ENM methodb yY oon et al [70] Based on the vibrational analysis on ENM-converted hIAPP fibrils, the lowest bending modes were observed. The elastic modulusw as then obtained by relating the continuum mechanics with the correspondingd eformation-mode eigenvalues.…”
Section: Influence Of the Aromatic Residue On The Materialc Haracterisupporting
confidence: 91%
See 1 more Smart Citation
“…[29] From their studies, the lowest frequency bending mode behavior was found to be similart ot he bending mode behavior of our model. In addition, the general trend of our resultsi sc onsistent with otherh IAPP results obtained by using the ENM methodb yY oon et al [70] Based on the vibrational analysis on ENM-converted hIAPP fibrils, the lowest bending modes were observed. The elastic modulusw as then obtained by relating the continuum mechanics with the correspondingd eformation-mode eigenvalues.…”
Section: Influence Of the Aromatic Residue On The Materialc Haracterisupporting
confidence: 91%
“…Previously,Y oon et al revealed the bending modes of hIAPP amyloid fibrils at the lowest frequencies. [54,70] To rsion and axial modes of hIAPP amyloid fibrils were also observed at higher frequencies.O ur resultss how similart endencies for bending and axial modes. In these modes, naturalf requencies reachedv alues in the ranges of 0.04-0.2 THz and 0.25-0.5 THz, respectively.H owever,a nalysiso ft he torsional mode gave different results to those obtained by Yoon et al;i nt his case, the torsional frequencies show lower values than those of the hIAPP amyloid fibrils.…”
Section: Influence Of the Aromatic Residue On The Materialc Haracterimentioning
confidence: 87%
“…Furthermore, the role of hydrophobic amino acids could be presented through the differences between the homo and hetero models, including parallel and antiparallel models. In contrast to time-force curves, material responses would be different and reflected the previous study, which revealed the polymorphic characteristics of hIAPP fibrils by solving eigenvalue problems [29].…”
Section: Materials Characteristics Of Polymorphic Hiapp Fibrilsmentioning
confidence: 86%
“…In our previous studies, we showed the material properties and characteristics of polymorphic hIAPP fibrils, which were evaluated via different types of deformation modes such as soft bending, stiff bending, torsion, and axial, using eigenvalue problems with ENM (elastic network model) and MD simulations [28,29]. Moreover, recently we studied the different material behaviors of hIAPP fibrils using constant bending simulations [30,31].…”
mentioning
confidence: 99%
“…They also applied ENM to calculate the mechanical properties of hIAPP amyloid fibrils. Despite this detailed chemical interaction information, each structure exhibited different mechanical properties related to differences in H-bond interactions [61]. Additionally, the effects of mutations on the mechanical properties of amyloid fibrils [62] or multi-strand effects can be calculated [63].…”
Section: Simulationsmentioning
confidence: 99%